Macrocirculatory Parameters and Oxygen Debt Indices in Pigs During Propofol Or Alfaxalone Anesthesia When Subjected to Experimental Stepwise Hemorrhage - Lervik, Andreas; Forr Toverud, Simen; Bohlin, Jon; Haga, Henning Andreas (Frontiers in Veterinary Science, 2021)
Background Pigs are anaesthetized when used for emergency procedures live tissue training (LTT) of civilian and military medical personnel or for experimental purposes, but there is a paucity in the literature regarding anesthesia of pigs for this purpose. Objective(s) The main goals of the study were to compare oxygen debt, macrocirculatory parameters and time to cardiac arrest between pigs in hemorrhagic shock and anaesthetized with propofol-ketamine-dexmedetomidine or alfaxalone-ketamine-dexmedetomidine. Design A prospective, non-blinded randomized study design was used. Sixteen pigs were randomized in blocks of four to be anaesthetized with either propofol-ketamine-dexmedetomidine (n=8) or alfaxalone-ketamine-dexmedetomidine (n=8) as a continuous infusion. Interventions Premedication with ketamine 15 mg kg-1 and midazolam 1 mg kg-1 was given i.m.. Anesthesia was maintained with propofol 8 mg kg-1 h-1 or alfaxalone 5 mg kg-1 h-1 combined with ketamine 5 mg kg-1 h-1 and dexmedetomidine 4 µg kg-1 h-1 i.v.. A stepwise, volume-controlled model for hemorrhage was created by exsanguination. Main outcome measures Indices of oxygen debt (lactate, base excess and oxygen extraction), macrocirculatory (PR, SAP, DAP, MAP and CI, SVI and TPR) variables, and time to death was compared between groups. Results Pigs in the alfaxalone group had significantly higher SAP than pigs given propofol. No difference in other macrocirculatory variables or indices of oxygen debt could be found. A blood loss of 50% of the total blood volume or more was possible in most pigs with both anesthetic regimes. Conclusions Pigs anaesthetized with propofol or alfaxalone combined with ketamine and dexmedetomidine tolerated substantial blood loss.